PROPHET MUHAMMAD’S RHETORIC; An Analysis of Prophet Muhammad Speech on Wada’ Pilgrim in Sahih al-Bukharī - Khatibah Khatibah Khatibah; Nawir Yuslem; Abdullah Abdullah (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2018)
The study aims to analyze more in depth about the rhetoric used by Prophet Muhammad SAW in Haji Wada '. The main data sources in this study are the hadiths narrated in Sahih Bukhari and Sahih Muslim. The method used in this research is descriptive qualitative where the researcher describes the theoretical meaning contained in the speech of Prophet Muhammad SAW at the time of Haji Wada 'which is in time in Shahih Bukhari and Sahih Muslim. The results of this study are as follows: 1} The enthusiasm of the audience to listen to the sermon of Prophet Muhammad SAW is proof that the Prophet was  very beloved by his people, they are very confident with what the Prophet said, so their faith becomes increased when listening to the speech of Prophet SAW in the Hajj. Predicted, Audiences who participated in the Hajj up to 140 million people. 2} socially, the rhetoric used by Prophet Muhammad SAW in Haji Wada 'was able to raise the spirit of the Muslims, so that Prophet Muhammad SAW is able to evoke the spirit of Islamic economy, because one of the focus of the sermon was the independence of the people in the field of economy. In conclusion, the rhetoric of Prophet Muhammad SAW in the Hajj Wada 'was a very important thing to be used as a reference for the development of the ummah